Mac OS X - Pogue, David, 1963- (Missing manual., 2002)
New York Times computer columnist David Pogue has just updated his bestselling Mac OS X: The Missing Manual! And once again, he applies his scrupulous objectivity to this exciting new operating system, revealing which new features work well and which do not. With new material on almost every page, this second edition offers a wealth of detail on the myriad changes in OS X 10.2. Pogue includes new chapters on iChat (Apple's new, AOL-compatible instant-messaging software), Sherlock 3 (the Web search tool that pulls critical Web information directly onto the desktop), and the new Finder (which reintroduces--spring-loaded--folders by popular request). With humor and technical insight characteristic of the Missing Manual series, the book also delves into features under the hood, such as the networking tools that allow Macs and PCs to swap files on a network. This acclaimed book is an essential resource for anyone who is serious about Mac OS.